Dry eye disease - Wolffsohn, James (Henry Stewart Talks, 2018)
Function of the tear film, TFOS DEWS II report, Definition and classification of dry eye disease, Epidemiology of dry eye disease, Pathophysiology of dry eye disease, Available diagnostic methodology, Management and Therapy of dry eye disease